Pedagogical Competence of Non-Muslim Teachers in Teaching Islamic Education at SDN 3 Pundu - Endah Hana Kaliwahyuni; Muslimah Muslimah; Abdullah Abdullah (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the pedagogical competencies of non-Muslim teachers in teaching Islamic Religious Education (IRE) at SDN 3 Pundu and to identify the challenges and solutions encountered in its implementation. This study employs a qualitative approach with a case study design. The research subjects consist of non-Muslim teachers as primary informants, the school principal, and students as supporting informants. Data collection techniques include observation, interviews, and documentation, while data analysis utilizes an interactive model encompassing data reduction, data presentation, and drawing conclusions, with validity testing through triangulation. The results of the study indicate that the pedagogical competencies of non-Muslim teachers fall into the adequate to good category, particularly in the aspects of understanding students, planning, and implementing instruction. However, there are limitations in their mastery of religious subject matter and the practice of worship. The main challenges include limited understanding of the substance of Islamic Education (PAI), sensitivity to religious values, and a lack of specialized training. To address this issue, teachers and schools have implemented various measures, such as collaborating with teachers of other subjects, utilizing educational media, and providing institutional support. This study concludes that strong pedagogical competencies and adaptive strategies enable Islamic Education (PAI) instruction to remain effective even when taught by non-Muslim teachers. Therefore, strengthening competencies and policy support are necessary to maintain the quality of instruction within the context of limited resources.